Enhanced Oral Bioavailability of 2‑(Phosphonomethyl)-pentanedioic Acid (2-PMPA) from its (5-Methyl-2-oxo-1,3-dioxol-4-yl)methyl (ODOL)-Based Prodrugs - Dash, Ranjeet P; Tichý, Tomáš; Veeravalli, Vijayabhaskar; Lam, Jenny; Alt, Jesse; Wu, Ying; Tenora, Lukáš; Majer, Pavel; Slusher, Barbara S; Rais, Rana (Molecular pharmaceutics, 2019)
2-(Phosphonomethyl)-pentanedioic acid (2-PMPA) is a potent (IC50 = 300 pM) and selective inhibitor of glutamate carboxypeptidase II (GCPII) with efficacy in multiple neurological and psychiatric disease preclinical models and more recently in models of inflammatory bowel disease (IBD) and cancer. 2-PMPA (1), however, has not been clinically developed due to its poor oral bioavailability (<1%) imparted by its four acidic functionalities (c Log P = −1.14). In an attempt to improve the oral bioavailability of 2-PMPA, we explored a prodrug approach using (5-methyl-2-oxo-1,3-dioxol-4-yl)methyl (ODOL), an FDA-approved promoiety, and systematically masked two (2), three (3), or all four (4) of its acidic groups. The prodrugs were evaluated for in vitro stability and in vivo pharmacokinetics in mice and dog. Prodrugs 2, 3, and 4 were found to be moderately stable at pH 7.4 in phosphate-buffered saline (57, 63, and 54% remaining at 1 h, respectively), but rapidly hydrolyzed in plasma and liver microsomes, across species. In vivo, in a single time-point screening study in mice, 10 mg/kg 2-PMPA equivalent doses of 2, 3, and 4 delivered significantly higher 2-PMPA plasma concentrations (3.65 ± 0.37, 3.56 ± 0.46, and 17.3 ± 5.03 nmol/mL, respectively) versus 2-PMPA (0.25 ± 0.02 nmol/mL). Given that prodrug 4 delivered the highest 2-PMPA levels, we next evaluated it in an extended time-course pharmacokinetic study in mice. 4 demonstrated an 80-fold enhancement in exposure versus oral 2-PMPA (AUC0–t : 52.1 ± 5.9 versus 0.65 ± 0.13 h*nmol/mL) with a calculated absolute oral bioavailability of 50%. In mouse brain, 4 showed similar exposures to that achieved with the IV route (1.2 ± 0.2 versus 1.6 ± 0.2 h*nmol/g). Further, in dogs, relative to orally administered 2-PMPA, 4 delivered a 44-fold enhanced 2-PMPA plasma exposure (AUC0–t for 4: 62.6 h*nmol/mL versus AUC0–t for 2-PMPA: 1.44 h*nmol/mL). These results suggest that ODOL promoieties can serve as a promising strategy for enhancing the oral bioavailability of multiply charged compounds, such as 2-PMPA, and enable its clinical translation.